The combined application of swine manure and straw strips to the field can promote the decomposition of corn straw in “broken skin yellow” of black soil - Shuang Zheng; JingYing Liu; Liming Sun; Jinggui Wu (BMC Plant Biology, 2025)
Abstract Straw return is widely acknowledged as a crucial strategy for enhancing soil fertility and increasing crop yields. However, the continuous addition of straw, its slow decomposition, and retention can hinder crop growth. Therefore, it is essential to elucidate the characteristics of the crop straw decomposition. This study aims to explore the alterations in straw decomposition rates, as well as the content and structure of organic components, under the combined application of swine manure and corn straw in the broken skin yellow soil of black soil over time. The findings revealed that the straw decomposition rates in all treatments increased rapidly in the early stage, gradually slowed down and stabilized in the later stage. The decomposition rates of cellulose and hemicellulose were generally consistent with those of straw, while lignin decomposed more rapidly in the middle and later stages. Notably, the decomposition rate of straw and its components was significantly higher under the combined application of swine manure and biochar compared to other treatments, with decomposition rates of straw, cellulose, hemicellulose, and lignin recorded at: 66.16%, 63.38%, 61.16% and 47.96%, respectively, after 360 days. This treatment exhibited the most substantial damage to the apparent structure of corn straw over time, and it resulted in lower C/N ratios and the most pronounced decrease in the intensity of absorption peaks. Among all the treatments, the alkyl carbon/alkoxy carbon ratio was highest in the SCZ treatment, indicating that the addition of swine manure and biochar can significantly enhance straw decomposition. Correlation analysis revealed that the decomposition rates of straw, cellulose, hemicellulose, and lignin were significantly and positively correlated with the rates of alkyl carbon, aromatic carbon, and phenolic carbon in the organic functional groups of straw residues, and significantly negatively correlated with alkoxy carbon. The study suggested that the combined application of straw, swine manure and biochar in the field can effectively promote the decomposition of corn straw. Our findings provided insights into the efficient utilization of various exogenous conditioners, serving as a scientific basis for accelerating straw decomposition and enhancing nutrient utilization.